UNGKAPAN BAHASA ALE RASA BETA RASA DALAM KOMUNIKASI SOSIAL DI MALUKU DAN PEMBENTUKAN KARAKTER - Wenno, I. H. (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
According to the sosiocultural context, language â€œale rasa beta rasaâ€ have a deep meaning for the people of Maluku. More than a concept, this phrase have a cultural meaning that can inspire people in Maluku about life, as well as social relationship among people, such as relation between individuals, groups, villages, ethnics, and religions.Â  The meaning and value of â€œale rasa beta rasaâ€ can be used to solve conflict and to prevent a social chaos among the people. This idiom, can be used to increase developmentÂ  and to make a good relation between goverment and people as a civil society. In daily life, this culture can be a model to increase a better social relatonship and affection each other. This culture is a local wisdom that can be used to develop character building and to unite the people and to stabilize the nation.Keywords: Ale Rasa Beta Rasa, Komunikasi, Pembentukan Karakter